FluidityProject/fluidity: New test cases "Analytical solutions for mantle flow in cylindrical and spherical shells" - Kramer,S; Wilson,C; Davies,R; Funke,SW; Greaves,T; Avdis,A; Lange,M; Candy,A; Cotter,CJ; Pain,C; Percival,J; Mouradian,S; et al. (2020)
This release adds new test cases described in the GMD paper "Analytical solutions for mantle flow in cylindrical and spherical shells"